Pengaruh Dimensi Kualitas Layanan Terhadap Kepuasan Nasabah Simpan Pinjam - Winata, Made Mardhi; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2013)
This study aimed to determine the effect of the dimensions of service quality on customer satisfaction savings and loans co-operative civil township Bali governor's office. The sample in this study using purposive sampling, processing data using SPSS 15.0 for Windows. The results obtained show that the effect of service quality dimensions simultaneously and partially on customer satisfaction savings and loans co-operative civil township Bali governor's office. Keywords : direct evidence, reliability, responsiveness, assurance, empathy, customer satisfaction